Longitudinal alterations in nutrient intake and food pattern in patients with non‐small cell lung cancer during anti‐neoplastic treatment: a cohort study. Issue 5 (10th April 2019) - Tobberup, R.; Holst, M.; Carus, A.; Jensen, N. A.; Falkmer, U. G.; Rasmussen, H. H.
Abstract: Background: Unintentional weight loss is frequently observed in cancer patients. Nutritional therapy is essential, and dietary counselling is the first step. The present study aimed to explore the nutrient intake and food patterns in weight‐stable and weight‐losing patients with non‐small cell lung cancer (NSCLC) during anti‐neoplastic treatment. Methods: Patients with NSCLC ( n  =   62) were observed during first‐line systemic anti‐neoplastic treatment. Body weight and dietary intake were assessed on the first and second cycle, and after completing three cycles of treatment. Longitudinal changes were analysed in three groups: weight stable, weight losers and mixed weight . Results: Nutrient intake did not change during treatment in weight stable, although weight losers significantly increased the relative protein intake. Weight stable maintained the food pattern during treatment apart from a decreased consumption of oral nutritional support (ONS). At baseline, weight losers were characterised by pretreatment weight loss, high consumption of ONS, as well as low consumption of grains and animal products. During treatment, weight losers increased the consumption of protein, fatty foods and ONS but decreased the consumption of sweets and alcohol. Conclusions: Large heterogeneity in nutrient and food intake was observed in NSCLC patients during anti‐neoplastic treatment. Weight losers and weight stable had a similar nutrient intake although protein intake increased in weight losers . Grains and animal products were lower and ONS higher in weight losers compared to weight stable during treatment. Weight losers further increased the consumption of ONS and fatty foods, while the consumption of sweets and alcohol decreased during treatment.